Are tourism and conservation compatible for 'island tame' species? - Worrell, T.; Admiraal, R.; Bateman, Bill; Fleming, P. (The Zoological Society of London, 2016)
© 2016 The Zoological Society of London.Islands play an important conservation role due to high rates of speciation as well as providing a predator-free refuge environment for species that are vulnerable to terrestrial predation on the mainland. Many animals show marked 'island tameness' on predator-free islands, reducing costly escape responses in the absence of predation threat. Island tameness also translates to altered responses toward humans, making many island species attractive for wildlife tourism. We explored temporal and spatial differences in behavioral responses in the Rottnest Island quokka Setonix brachyurus. This marsupial is an excellent species to test for the effects of ecotourism, as well as of being conservation significance (IUCN-listed as vulnerable). Comparing escape responses for n = 339 individuals in high tourism and low tourism seasons, quokkas at tourism sites allowed a person to approach closer before moving away compared with non-tourisms sites, and two-thirds of individuals around tourism sites allowed a person to approach within 1 m (compared with 14% of individuals at non-tourism sites). For n = 67 ad hoc interactions with tourists, quokkas would only move away from an interaction with a tourist when the tourist group was noisy or there was an attempt to touch the animal. Time budgets (n = 379 individuals) showed that quokkas spent more time in group behavior and locomotion, but less in vigilance and feeding for tourism sites compared with non-tourism sites. Understanding the impact of ecotourism on animal behavior will help to frame conservation management actions to ensure persistence of threatened wildlife species. We propose two models describing animal responses toward ecotourism: spatial separation according to animal temperament or temporal adjustment due to learned habituation. These models are not mutually exclusive and we suggest that both spatial separation and habitation are likely evident for Rottnest quokkas. We discuss the implications of these results for protection of animals on the island as well as for species conservation.